A Standard Algorithm for Reconstruction of Scalp Defects With Simultaneous Free Flaps in an Interdisciplinary Two-Team Approach - Weitz, Jochen; Spaas, Christophe; Wolff, Klaus-Dietrich; Meyer, Bernhard; Shiban, Ehab; Ritschl, Lucas M. (Frontiers in Oncology, 2019)
Abstract: Reconstructions of complex scalp after ablative resection or by post-traumatic tissue loss, can present difficulties regarding recipient vessel selection, functional and aesthetic outcome. The harvesting method for many microvascular free flaps requires a need for changing patients position during surgery and makes a simultaneous interdisciplinary two-team approach complicated, which is a major disadvantage regarding safety and operation time. The ideal flap for scalp reconstruction has yet to be described, although the microvascular latissimus dorsi flap is frequently referred to as the first choice in this context, especially after resection of large defects. The purpose of this study is to compare two different microvascular free flaps for a simultaneous scalp reconstruction in an interdisciplinary two-team approach applying a standardized algorithm. All consecutively operated complex scalp defects after ablative surgery from April 2017 until August 2018 were included in this retrospective study. The indications were divided into neoplasm or wound healing disorder. Two microvascular flaps (latissimus dorsi or parascapular flap) were used to cover the soft tissue component of the resulting defects. 17 patients met the inclusion criterion and were treated in an interdisciplinary two-team approach. Skull reconstruction with a CAD/CAM implant was performed in 10 cases of which 4 were in a secondary stage. 9 patients received a parascapular flap and 8 patients were treated with latissimus dorsi flap with split thickness skin graft. Anastomosis was performed with no exception to the temporal vessels. One parascapular flap had venous insufficiency after one week followed by flap loss. One latissimus dorsi flap had necrosis of the serratus part of the flap. All other flaps healed uneventful and could be further treated with adjuvant therapy or CAD/CAM calvarial implants. Regarding overall complications, flap related complications, flap loss and inpatient stay no statistical differences were seen between the diagnosis or type of reconstruction. The parascapular flap seems to be a good alternative for reconstruction of complex tumor defects of the scalp besides the latissimus dorsi flap. Stable long-term results and little donor site morbidity are enabled with good aesthetic outcomes and shorter operation time in an interdisciplinary two-team approach.